2022
DOI: 10.1136/bmjopen-2022-061954
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of tenotomy versus tenodesis for long head of biceps pathology: a systematic review and meta-analysis

Abstract: ObjectivesThe comparative clinical effectiveness of common surgical techniques to address long head of biceps (LHB) pathology is unclear. We synthesised the evidence to compare the clinical effectiveness of tenotomy versus tenodesis.DesignA systematic review and meta-analysis using the Grading of Recommendations Assessment, Development and Evaluation approach.Data sourcesEMBASE, Medline, PsycINFO and the Cochrane Library of randomised controlled trials were searched through 31 October 2021.Eligibility criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Moreover, in our study, none of the patients reported any cosmetic complications in the tenodesis or biceps area, and none of the patients had any report indicating Popeye sign. This finding accords with previous reports [39,40] and especially in a meta-analysis of Level I randomized control trials by Belk et al [39]. The latter authors compared biceps tenotomy with tenodesis and found that it reportedly had a higher rate of cosmetic deformity [39].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in our study, none of the patients reported any cosmetic complications in the tenodesis or biceps area, and none of the patients had any report indicating Popeye sign. This finding accords with previous reports [39,40] and especially in a meta-analysis of Level I randomized control trials by Belk et al [39]. The latter authors compared biceps tenotomy with tenodesis and found that it reportedly had a higher rate of cosmetic deformity [39].…”
Section: Discussionsupporting
confidence: 91%
“…We also noted muscle cramps and a slight loss of strength in flexion with supination of the elbow, as described in the literature. (16) Several studies have compared the functional results of tenotomy and tenodesis in the treatment of LB tendinopathy, with no clinical or functional difference between the two techniques. in fact, even with a low rate, but we can also have a Popeye sign with tenodesis.…”
Section: Discussionmentioning
confidence: 99%
“…This technique produces additional therapeutic effects for patients who have biceps pathology, such as tendonitis or biceps instabilities, in addition to the rupture of the cuff, since it has a tenotomy effect, a technique with widely demonstrated benefits. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 , 17 , 18 , 30 There are risks associated with LHB tenotomy, such as the appearance of Popeye’s sign or cramps, although over time, they rarely represent a functional problem in patients. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%